MAKAKO Program (Mengaji Kala Corona) to Increase Self Awareness Children During the Pandemic Covid-19 - Indah Fatmawati; Anisa Rahmadani (Jurnal Pengabdian Pada Masyarakat, 2021)
The background behind this community service is caused of the impact of the COVID-19 pandemic which has mad face-to-face lessons in schools become online learning and places learning Al-Qur’an are recently closed. This caused the children in scavenger stalls, West Jakarta to lose their places to learn especially in learning AL-Qur’an. So MAKAKO (Mengaji Kala Korona) present to be a place where children can learn Al-Qur’an and increase self-awareness with classical guidance programs. The program is carried out with an online system, using Voice Call and Video Calls as the medium The results of the activity are the children will show on paper and then they will send photos and presentation videos. The MAKAKO program has succeeded in being place for children to continue learning Al-Qur’an and increase self-awareness based on three-component references; Emotional Self -Awareness, Accurate Self-Awareness, and Self-Confident.